Draft Annual Plan 1988-89 Vol-III Government of Tripura - Planning Commission (Planning Commission, 1988)
The income level of the family per annum to determine the poverty line has been raised from Rs. 3500 to 4300/-. However, priority is given in Tripura to those below the poverty line of Rs. 3500/-. The families are selected from the poorest section’, in rural areas in consultation with Gaon Panchayat and on the basis of the information collected through surveys The schemes to be implemented by the individual family with credit from Bank and subsidy from Govt-. are formulated by the Joint teams in consultation was h Gaon P-panchayat, c one erne d bank & beneficiaries on the basis of the resources and input availabilities. The joint team consists of the officers of the DRDA, Block, Bank and Development Deptts.
Government of Tripura